Anti-Malassezia-Specific IgE Antibodies Production in Japanese Patients with Head and Neck Atopic Dermatitis: Relationship between the Level of Specific IgE Antibody and the Colonization Frequency of Cutaneous Malassezia Species and Clinical Severity - Zhang, Enshi (Hindawi Publishing Corporation, 2011)
Atopic dermatitis of the head and neck (HNAD) is recognized as a separate condition. Malassezia, the predominant skin microbiota fungus, is considered to exacerbate atopic dermatitis (AD), especially HNAD. In the present study, we investigated the relationships between the levels of specific IgE antibodies, colonization frequency of eight predominant Malassezia species, and clinical severity in 61 patients with HNAD (26 mild, 24 moderate, and 11 severe cases). As clinical severity increased, the levels of specific IgE antibodies against eight Malassezia species also increased. Species diversity of the Malassezia microbiota in scale samples from patients was analyzed by nested PCR using species-specific primers. The clinical severity of HNAD was correlated with the total level of specific IgE antibodies against Malassezia species and the number of Malassezia species detected.